Study On Corporate Entrepreneurial Strategies: A Case Of Gulfsands Petroleum PLC - Mahlouji, Hamed (2010)
In this study, Gulfsands Petroleum\'s internal and external environments are examined. A Strategy Formulation Framework designed by David (1986) is used to recommend the most feasible corporate entrepreneurial for Gulfsands Petroleum to take forth based on based its current environmental conditions.The finding shows that risk reducing strategies are generally more feasible.